NPC-Exosome Carry Wild and Mutant-type p53 among Nasopharyngeal Cancer Patients - Hamsu Kadriyan; Eka Sunarwidhi Prasedya; Nova Audrey Luetta Pieter; Masyita Gaffar; Amsyar Akil; Agusalim Bukhari; Budu Budu; Andi Alfian Zainuddin; Rina Masadah; Achmad Chusnu Romdhoni; Abdul Qadar Punagi (The Prodia Education and Research Institute (PERI), 2021)
BACKGROUND: Nasopharyngeal cancer (NPC) is known to release a specific exosome. NPC-derived exosome (NPC-Exo) could carry p53. However, information regarding the type of p53 carrier on NPC-Exo remains limited. This study aims to introduce our important findings regarding the type of p53 NPC-Exo cargo.METHODS: Serum from patients with NPC were prepared for exosome isolation with Seramir Exoquick by following the manual instructions. RT-PCR was conducted to determine the expression levels of latent membrane protein 1 (LMP-1) and p53 in the exosome isolate. Partial sequencing of p53 amplicon was conducted to determine mutation type of p53.RESULTS: There were 8 patients enrolled in this study. According to RT-PCR results, the expression levels of LMP-1 and p53 varied in the NPC-Exo isolate. Based on sequencing analysis, 1 case of p53 mutation was noticeable.CONCLUSION: According to current results, the NPC-derived exosome potentially carries not only wild type but also mutant type p53. Further research is needed to explore deeper the effect of the mutant type p53 as an exosome carrier in the clinical application.KEYWORDS: Nasopharyngeal cancer, exosome, p53, mutation